2023
DOI: 10.1111/ocr.12649
|View full text |Cite
|
Sign up to set email alerts
|

Bulk RNA‐seq analyses of mandibular condylar cartilage in a post‐traumatic TMJ osteoarthritis rabbit model

Abstract: ObjectiveThe temporomandibular joint (TMJ) is anatomically comprised of the mandibular condylar cartilage (CC) lined with fibrocartilaginous superficial zone and is crucial for eating and dental occlusion. TMJ osteoarthritis (OA) leads to pain, joint dysfunction and permanent loss of cartilage tissue. However, there are no drugs clinically available that ameliorate OA and little is known about global profiles of genes that contribute to TMJ OA. Furthermore, animal models that recapitulate the complexity of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Similarly, bulk RNA sequencing of the TMJ condyle in a rabbit model of osteoarthritis (OA) has identified Wnt, Notch and PI3K-Akt signalling pathways as key to the development of TMJ OA. 73 Transcriptome sequencing during orthodontic tooth movement (OTM) in mice have revealed differentially expressed genes that are involved in hypoxia, inflammatory and bone remodelling pathways. 74 Despite their nascent status, the future promise of omics discoveries to orthodontic therapies and risk assessment can be envisioned from the current examples of individualized biotherapeutics.…”
Section: Omics In Craniofacial Growth Dentofacial Orthopaedics and Or...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, bulk RNA sequencing of the TMJ condyle in a rabbit model of osteoarthritis (OA) has identified Wnt, Notch and PI3K-Akt signalling pathways as key to the development of TMJ OA. 73 Transcriptome sequencing during orthodontic tooth movement (OTM) in mice have revealed differentially expressed genes that are involved in hypoxia, inflammatory and bone remodelling pathways. 74 Despite their nascent status, the future promise of omics discoveries to orthodontic therapies and risk assessment can be envisioned from the current examples of individualized biotherapeutics.…”
Section: Omics In Craniofacial Growth Dentofacial Orthopaedics and Or...mentioning
confidence: 99%
“…Transcriptomic studies on the developing mouse sutures have shown distinct RNA profiles and cellular signatures and localization 72 that provide a roadmap to future studies to identify customized therapies for craniosynostosis. Similarly, bulk RNA sequencing of the TMJ condyle in a rabbit model of osteoarthritis (OA) has identified Wnt, Notch and PI3K‐Akt signalling pathways as key to the development of TMJ OA 73 . Transcriptome sequencing during orthodontic tooth movement (OTM) in mice have revealed differentially expressed genes that are involved in hypoxia, inflammatory and bone remodelling pathways 74 .…”
Section: Application Of Biologics and Multi‐omics In Precision Orthod...mentioning
confidence: 99%